2010
DOI: 10.1007/s10620-009-1112-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Carbon Monoxide Ameliorates TNBS-Induced Colitis in Mice Through the Inhibition of TNF-α Expression

Abstract: The inhalation of CO protected mice from developing intestinal inflammation. Based on these data, the beneficial effects of CO in a murine colitis model may be attributed to its anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…[5][6][7][8] The heme oxygenase (HO) group of enzymes, of which HO-1 is inducible in immune cells, mediate heme degradation, generating equimolar amounts of iron, biliverdin, and CO. We and others have demonstrated that the HO-1/CO pathway can regulate intestinal inflammation in experimental models of acute and chronic intestinal inflammation. [9][10][11][12][13] Indeed, in our work, anti-inflammatory effects of CO required the induction of HO- 12 Our work leads to a model where, in the local microenvironment of the intestine, CO and HO-1 are components of an evolutionarily conserved homeostatic pathway modulated in health and disease by cross-talk between the microbiota and the mucosal immune compartment.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…[5][6][7][8] The heme oxygenase (HO) group of enzymes, of which HO-1 is inducible in immune cells, mediate heme degradation, generating equimolar amounts of iron, biliverdin, and CO. We and others have demonstrated that the HO-1/CO pathway can regulate intestinal inflammation in experimental models of acute and chronic intestinal inflammation. [9][10][11][12][13] Indeed, in our work, anti-inflammatory effects of CO required the induction of HO- 12 Our work leads to a model where, in the local microenvironment of the intestine, CO and HO-1 are components of an evolutionarily conserved homeostatic pathway modulated in health and disease by cross-talk between the microbiota and the mucosal immune compartment.…”
Section: Introductionmentioning
confidence: 66%
“…[9][10][11]14 Importantly, CO exposure and HO-1 induction have been shown to ameliorate colitis in numerous experimental models of IBD with different immunopathogeneses, highlighting the importance of this pathway as a homeostatic checkpoint in intestinal immune responses. [9][10][11]13,14,21 Using Il10 −/− mice as a model of microbiota dependent, IL-12/23-mediated chronic intestinal inflammation, we demonstrated that exposure to CO ameliorated colitis in an HO-1 dependent manner.…”
Section: Ho-1/co Ameliorate Colitis Through Altered Cytokine Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have demonstrated CO-dependent protection in animal models of inflammatory syndromes, including sepsis [9] and colitis [10]. Inhalation of CO significantly suppresses ischemic induction of PAI-1 expression and the accumulation of fibrin in mice [11].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, CO, a prominent component of CS long considered as just being a toxic gas [68], was recently shown to exert potent cell protective effects because of its anti-inflammatory, anti-apoptotic and anti-oxidant capabilities [69,70]. In three different studies, inhaled CO consistently decreased inflammation in chemically induced and genetic mouse models of UC and CD, respectively [71][72][73]. In particular, the same group of researchers [71,72] exposed two different knockout mouse models, IL-10 −/− [74] and TCRα −/− [75,76], to CO at a concentration of 250 ppm (part per million) or compressed air (control), attempting to recapitulate, at least in part, CS effects on the development of CD and UC, respectively.…”
Section: Inhalation Studies Investigating the Effect Of Cs In Rodent mentioning
confidence: 99%